Pengaruh Pro Active Personality Terhadap Subjective Success Career pada Karyawan PT. Bank Rakyat Indonesia Persero Tbk. Cabang Tondano - Frauli Tatilu; Jofie Hilda Mandang; Meike Endang Hartati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence of proactive personality on subjective career success in PT employees. Bank Rakyat Indonesia (BRI) Persero Tbk. Tondano Branch. The method used in this research is a quantitative method with a crosssectional approach, involving 56 employees who were respondents taken using a saturated sample. The data collection instruments are the Proactive Personality Scale and the Subjective Career Success Scale which have been tested for validity and reliability. The results of a simple analysis using simple linear regression show that there is a significant positive influence between Proactive Personality and subjective Success Career, with a significant value of 0.00<0.05 and a coefficient of determination (R²) of 0.204, meaning that 20.4% of the subjective Success Career variable is influenced by proactive personality and the other 79.6% is influenced by variables not examined in this research. These results show that the higher the level of proactive personality, the higher their perception of their subjective career success.